Comparative analysis of approaches to assessing the market cost of business in domestic and foreign practice - El. N. Gavrilova; D. N. Hasjanova (Вестник университета)
The greatest demand in the modern world is for business valuation service. Valuation activity makes it possible to identify the important characteristics of a particular business which is necessary for making management decisions by company owners. The results of business valuation are used to determine existing perspectives: the presence of investment opportunities, ways to optimise business processes, need to expand business activities, etc. According to statistics, several decades ago, business valuation was conducted in no more than 10 % of cases. Currently, on the contrary, more than 90 % of companies are interested in regular valuation. However, the widespread demand for business valuation has made it possible to find a number of pressing problems that need to be solved in the future. One of the most serious сhallenges is the existence of problem areas in the national legal framework. The work examines the process of business valuation using basic methods and approaches, analyses the foreign experience on the research topic and also valuates a domestic enterprise in different ways. The authors concluded that it is necessary to choose the method that can be most effective in valuating a particular enterprise in particular conditions.